TINJAUAN YURIDIS TERHADAP PERINTAH MEMBUBARKAN DIRI OLEH PEMERINTAH KEPADA KERUMUNAN MASSA UNTUK MENGHINDARI CORONA VIRUS DEASES 2019 (COVID-19) BERDASARKAN PASAL 218 KITAB UNDANG-UNDANG HUKUM PIDANA - Yuki Heruyadi (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTGenerally, this event is called an Extraordinary Event (KLB) and can cause an outbreak that attacks the wider community in a short time caused by infectious diseases. On the other hand, the impact of the development of science and technology today has led to new discoveries of infectious diseases that are increasing and difficult to treat, for example, Corona Virus Diseases 2019 or COVID-19 as it is today. The head of the Indonesian National Police (Kapolri) General Idham Azis said his party had dispersed thousands of crowds on the grounds of preventing the spread of the corona virus (Covid-19). The dissolution was carried out since the publication of the Indonesian Police Chief's Declaration on March 19, 2020. The mass dissolution was also accompanied by an education program for the public. The National Police used several rules as a basis for dissolution. First is Article 14 paragraph (1) and paragraph (2) of Law Number 4 of 1984 concerning Infectious Disease, Article 93 of Law Number 6 of 2018 concerning Health Quarantine, and Articles 212, 214, 216, and 217 of the Criminal Code.Based on the background described above, the authors formulated the problem as follows: 1). What is the legal aspect of the order to disperse by the government to the crowd to avoid the 2019 Corona Diseases Virus Outbreak Under Article 218 of the Criminal Code? 2). What is the role of the Indonesian National Police in the order to disperse by the authorities to the masses to avoid the 2019 Corona Diseases Virus Outbreak Under Article 218 of the Criminal Code?So it can be concluded: 1). To anticipate and deal with the impact of COVID-19 transmission, the Regional Head established the Regional COVID-19 Task Force for Acceleration Handling based on the considerations and recommendations of the Chairperson of the Implementing Task Force for the Handling of the COVID-19 Handling in accordance with the Presidential Decree regarding the Task Force for the Acceleration of COVID-19 Handling. 2). The role of the Community Police in handling the Covid-19 outbreak with the implementation of Large-Scale Social2Restrictions (PSBB) focuses on law enforcement with non-penal means spearheaded by Bhabinkamtibmas in collaboration with community leaders. Progressive steps taken by the Indonesian National Police include the assignment of Bhabinkamtibmas in each village / kelurahan. The form of optimizing non-legal channels in the sense of finding a meeting point in deliberation and consensus efforts that includes all criteria in consensus in the peace process outside the judiciary by means of mediation or deliberation in achieving a fairness expected by the parties involved in handling the Covid-19 outbreak to find the best solution that is agreed and agreed by the parties.Keywords: Covid-19 Handling, Dispersal, Mass Crowds